Natural Killer Cells: Development, Maturation, and Clinical Utilization - Abel, Alex M.; Yang, Chao; Thakar, Monica S.; Malarkannan, Subramaniam (Frontiers in Immunology, 2018)
Natural killer cells are the predominant innate lymphocyte subsets that mediate anti-tumor and anti-viral responses, and therefore possess promising clinical utilization. NK cells do not express polymorphic clonotypic receptors and utilize inhibitory receptors (KIR and Ly49) to develop, mature, and recognize ‘self’ from ‘non-self’. The essential roles of common gamma cytokines such as IL-2, IL-7, and IL-15 in the commitment and development of NK cells are well-established. However, the critical functions of proinflammatory cytokines IL-12, IL-18, IL-27, and IL-35 in the transcriptional-priming of NK cells are only starting to emerge. Recent studies have highlighted multiple shared characteristics between NK cells the adaptive immune lymphocytes. NK cells utilize unique signaling pathways that offer exclusive ways to genetically manipulate to improve their effector functions. Here, we summarize the recent advances made in the understanding of how NK cells develop, mature, and their potential translational use in the clinic.